Hubungan Berat Badan Lahir dengan Ruptur Perineum pada Persalinan Normal di Puskesmas di Tunong - Nurrahmaton Nurrahmaton; Elvi Era Liesmayani; Burna Safira (Jurnal Bidan Mandiri, 2023)
Rips through the birth canal is a form of obstetric trauma is one of the causes of the high maternal mortality rate in Indonesia. Perineal laceration occurs in almost all deliveries are the first and often also on the next delivery. Data in Puskesmas Idi Tunong in 2014 there were 249 maternal and a total of 112 (44.9%) were ruptured perineum, in 2015 there were 256 maternal and a total of 143 (55.8%) were ruptured perineum. This study aims to determine the relationship of birth weight with perineal rupture in normal deliveries at health centers Idi Tunong. This study used analytic survey with cross sectional study design. The samples were all mothers giving birth at health centers Idi Tunong the period January-April 2016 was 49 maternal. Data were analyzed by Chi-Square test. The results were obtained birth weight infants majority had normal birth weight as many as 42 infants (85.7%) infants. Normal child birth majority of ruptured perineum as much as 29 (59.2%). Statistical test results obtained by value p (sig) = 0.040 <0.05; then the hypothesis is accepted, which means that there is a relationship between birth weight with rupture of the perineum in Puskesmas Idi Tunong 2016. Suggested for health workers, especially midwives in order to increase knowledge and competence mainly in regards to the rupture of the perineum at birth mothers to reduce further complications to mothers who have ruptured perineum.